Histological Study on the Diameter of the Lymphoid Follicle of Vermiform Appendix in Bangladeshi People (Bangladesh Journal of Anatomy, 2010)
Context: The vermiform appendix is an abdominal organ performing the immunological function. Histological characteristics of this organ show its specialized immunological function. Vermiform appendix is involved in different disease processes such as appendicitis, carcinoma and diverticulitis. Appendicitis is the most important clinical condition. An appropriate anatomical knowledge about vermiform appendix is important for surgeons, pathologists and other physicians for proper diagnosis and management of appendicitis and carcinoma. Study design: Descriptive type of study. Place and period of the study: Department of Anatomy, Sir Salimullah Medical College, Dhaka from January 2006 to June 2007. Materials: Sixty (60) human postmortem vermiform appendix, age ranging from 0 to 65 years. Samples were collected from unclaimed dead bodies within 24 hours of death from the morgue of Sir Salimullah Medical College and Dhaka Medical College, Dhaka. Method: The samples were divided into five (5) different age groups. Result: Diameter of lymphoid follicles reduced with the advancing age and showed negative correlation with age which was highly significant (P